Defining the Meanings of “Great Books” in Contemporary Literature - Raekroon, Siwakorn (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2023)
In today's society, there are many factors that affect the value creation of “Great Books” depending on various factors as well as some contemporary literature books provide many definitions of the great books. This study presents characteristics of defining the “Great Books”, including three contemporary books: Ran Nang Sue Maew Hokkien (Hokkien Cat Bookshop) by Naruepon Sudsawad, Pha Thi Han Maew Lai Som Phu Phi Thak Nang Sue (The Cat Who Saved Books) by Sosuke Natsukawa, and Khwam Pliao Dai Un Kuek Kong Kern Than (Too Loud a Solitude) by Bohumi Hrabal. These books are defined as “Great Books” in numerous aspects. “Great Books” of contemporary literature are the fulfilment of emotions of individuals who struggle with despair as emotional healing. The books considered “Great Books” are required to succeed in fulfilling our understanding of human nature. It is made by authors’ writing strategies to convey how great the books are. The stories are narrated by different perspectives of the characters, mostly by the point of view of the protagonists. The narration is remarkable by adventurous themes. It is outstanding by expressing the emotional states of the characters that are lonely. Additionally, it is full of signs having spatial meanings, alienation, and emotions. The definition of “Great Books” is created by factors on the social level and individual levels. Hence, these are characteristics to attribute meanings of “Great Books” of contemporary literature that pinpoints its dynamic range of meanings of “Great Books”.